ダイ 24 ジ エットウ タイ リクジョウ セイブツ チョウサ ホウコク - 神田, 啓史; カンダ, ヒロシ; 佐藤, 博雄; サトウ, ヒロオ; 渡辺, 研太郎; ワタナベ, ケンタロウ; 高橋, 永治; タカハシ, エイジ; Kanda, Hiroshi; Satoh, Hiroo; Watanabe, Kentaro; Takahashi, Eiji (1986)
P(論文) 第24次越冬隊(1983-1984)が実施した環境モニタリングおよび露岩域における陸上生物調査の概要を報告した。環境モニタリングとしては例年どおり, 1) 大気中の炭酸ガス濃度測定, 2) 土壌中の細菌モニタリング用試料の採取, 3) 土壌中の藻類モニタリング用試料の採取, 4) 湖沼水モニタリング用試料の採取, 5) 大型動物センサスの5項目についての観測, 調査, 採集を行った。冬季(9月)に陸水のプランクトン採集を実施し, 季節変化を解明するための試料を得た。また, 東オングル島「中の瀬戸」付近の露岩, およびラングホブデ「雪鳥沢」の蘚類・地衣類群落調査を行い, 異なった群落の構成を持つ両地域の群落について, 年間を通じて季節的変化を考察する資料を得た。さらに, 生物隊員としては初めてやまと山脈地域での生物調査を行い, 地衣類を発見した。A群からG群までの各群の土壌試料を採取した。内陸露岩域の生態系の研究に有益な資料と思われる。 Records of environmental monitoring and field work of terrestrial biology, which were carried out from January 1983 to February 1984 as part of the winter programs of the 24th Japanese Antarctic Research Expedition (JARE-24), are briefly reported. The environmental monitoring consisted of measurement of CO_2 in the surface air at Syowa Station, sampling of water from five ponds selected for the monitoring, collection of soil samples for the study of survival of Eschericher coli under natural condition the floristic study of micro-algae in soil, and population census of the Adelie penguin, the Emperor penguin and the Weddell seal. Field studies of moss and lichen communities were undertaken in the ice-free areas along the Soya Coast and the Yamato Mountains. At a selected site near Naka-no-seto Strait, East Ongul Island, investigations on the relation between moss community and its micro-climatic conditions were made at intervals from February 1983 to January 1984. Observation of growth of moss blocks was conducted in a laboratory of Syowa Station and at an experimental site beside the laboratory. To obtain the information of eutrophication in the Antarctic environment, a succession of fresh water micro-algae in the water and the soil was artificially enriched for ten months under the natural condition. departmental bulletin paper